Self-Efficacy dan Burnout Akademik pada Mahasiswa yang Bekerja - Septriyan Orpina; Sowanya Ardi Prahara (Indonesian Journal of Educational Counseling, 2019)
SELF-EFFICACY AND ACADEMIC BURNOUT FOR WORKING STUDENTS. Academic burnout refers to stress, burden or other psychological factors because the learning process is followed by students so that it shows the state of emotional fatigue, tendency to depersonalization, and feeling of low personal achievement. There are individual factors that can affect burnout; one of the individual factors that can influence academic burnout is academic self-efficacy. This study aims to determine the relationship between academic self-efficacy and academic burnout in working students. Based on the results of research and discussion, it can be concluded that there is a negative relationship between academic self-efficacy and academic burnout on students who work. This means that the higher academic self-efficacy, the lower academic burnout in working students, conversely the lower of Academic self-efficacy, the higher academic burnout in working students.